Optimization of polyethylene terephthalate resin-brick formulation and design analysis for sustainable construction material - Adiyanto, Okka (2024)
Construction materials have embraced the use of recycled and renewable materials to meet sustainability goals, including plastic waste in the construction sector. One such use is in the creation of eco-bricks, which are environmentally friendly bricks made from waste materials. The primary raw material used in making eco-bricks is waste materials. With the increasing population and urbanization, plastic waste is on the rise and further processing is necessary to produce eco-friendly products like eco-bricks. However, a weakness in making eco-bricks lies in the adhesive or mixture used. Currently, some eco-bricks still use cement or clay as a binder, which requires further processing for drying and to increase compressive strength. A solution to this is using another type of adhesive that can improve the strength of eco-bricks, such as epoxy resin. Epoxy resin has high strength, durability, and the ability to protect against corrosion. It is also flexible and can be easily applied to different surfaces and with other materials. Therefore, in this research, a new type of eco-brick is made, namely PET-resin brick (PR-brick). PR-bricks are made using another type of adhesive, epoxy resin. The aim of this research is to optimize the material formulation and processing variables of PR-brick production and validate the performance, analyze the mechanical and thermal properties of the PR-brick and last is analyze environment impact of the production process of PR-brick. The method used in this research is RSM for formula optimization and processing variables of PRbrick. After the accuracy evaluation, PR-brick performance optimization statistical model has been developed. In this experiment Factor of Safety (FoS) and thermal properties were carried out on a base stand using Finite Element Method (FEM). The structural design and FEM analysis was carried out using SolidWorks software. In addition, LCA analysis is also used to analyze the impact of PR-Bricks on the environment. LCA Analysis adopted a gate-to-gate approach. This research aligns with the sustainable development goals (SDGs) program by promoting the use of environmentally friendly products through recycling. For the RSM is to determine the optimal mixture proportions in terms of ratio (%), particle size (mm), and drying time (days). The results show that the most suitable parameters for PR-brick production are a PET particle size of 1.14 mm, a mixing ratio of 89.97% and 6.92-days drying time based on RSM. Size 200x100x100 mm has a maximum FoS value than other shape. Size 200x100x100 has a value 6.544 for FoS. From the LCA PR-brick use of epoxy resin and PET as raw materials for eco-tiles has an impact on ozone formation (OF) of 118 m2 UES*ppm*hours, which is due to the use of epoxy resin chemicals as adhesives in the production of PR-Brick. The research indicates that this material mixture has a high potential for improving the compressive strength of PR-Brick. The results of the study indicate the use of epoxy resin and recycled PET in PRBrick production does not pose excessive environmental risks and does not significantly reduce the environmental profile.